Bone loss before the clinical onset of rheumatoid arthritis in subjects with anticitrullinated protein antibodies. Issue 5 (21st March 2013) - Kleyer, Arnd; Finzel, Stephanie; Rech, Jürgen; Manger, Bernhard; Krieter, Manuel; Faustini, Francesca; Araujo, Elisabeth; Hueber, Axel J; Harre, Ulrike; Engelke, Klaus; Schett, Georg
Abstract : Objective: Anticitrullinated protein antibodies (ACPA) are a major risk factor for bone loss in rheumatoid arthritis (RA). We have recently shown that ACPA directly induce bone loss by stimulating osteoclast differentiation. As ACPA precede the clinical onset of RA by years, we hypothesised that ACPA positive healthy individuals may already show skeletal changes. Methods: We performed a comparative micro-CT analysis of the bone microstructure in the metacarpophalangeal joints of ACPA positive and ACPA negative healthy individuals without clinical signs of arthritis. Results: ACPA positive (n=15) and negative (n=15) healthy individuals were not different in age (48.2±4.1 vs 51.4±3.8 years, p=0.57) or gender (eight women and two men in both groups). Bone mineral density was significantly reduced in ACPA positive individuals (mean±SEM 280±11 mg/cm 3 ) compared with controls (327±6). Bone loss was based on cortical bone changes, with significant (p=0.044) reduction in cortical thickness in the ACPA positive group (mean±SEM 0.22±0.03 mm) compared with controls (0.32±0.03 mm). Areas of cortical porosity were significantly (p=0.0005) more widespread in ACPA positive (mean±SEM 7.4±1.4%) than in ACPA negative individuals (1.0±0.3%). Discussion: Structural bone damage starts before the clinical onset of arthritis in subjects with ACPA. These findings revise the concept that bone damage is an exclusive consequence of synovitis in patients with RA.